Advantages of regenerated cellulose fibres as compared to flax fibres in the processability and mechanical performance of thermoset composites. (May 2016) - Santamala, H.; Livingston, R.; Sixta, H.; Hummel, M.; Skrifvars, M.; Saarela, O.
Abstract: Man-made cellulosic fibres (MMCFs) have attracted widespread interest as the next generation of fibre reinforced composite. However, most studies focused entirely on their performance on single fibre level and little attention has been paid to their behaviour on a larger application scale. In this study, MMCFs were utilized as reinforcement in unidirectionally (UD) manufactured thermoset composites and compared to several commercial UD flax fibre products. Specimens were prepared using a vacuum bag based resin infusion technique and the respective laminates characterized in terms of void fraction and mechanical properties. MMCF laminates had comparable or better mechanical performance when compared to flax fibre laminates. Failure mechanisms of MMCF laminates were noted to differ from those of flax-reinforced laminates. The results demonstrate the potential of MMCFs as a viable alternative to glass fibre for reinforcement on a larger scale of UD laminates. These results were utilized in the Biofore biomaterial demonstration vehicle.